Narcissistic aggression: lab-based and naturalistic approaches to establishing subtype differences - Smith, William (2022)
The thesis describes a series of experiments that explore different approaches to studying narcissistic aggression. These are an experimental psychology approach using behavioural tasks and eye-tracking, a purely psychometric approach using vignettes and self-report measures, and a more naturalistic qualitative approach using web-scraped data from online communities. The aim of these experiments is to develop more of a holistic understanding of narcissistic aggression and subtype differences in trait narcissism, whilst also providing insight into the viability of these approaches for future research.